Case report: Variants in the ERCC4 gene as a rare cause of cerebellar ataxia with chorea - Kulikowska, Joanna; Jakubiuk-Tomaszuk, Anna; Rydzanicz, Małgorzata; Płoski, Rafał; Kochanowicz, Jan; Kulakowska, Alina; Kapica-Topczewska, Katarzyna (Frontiers in Genetics, 2023)
Abstract. Variants of the ERCC4 gene have been described in association with the following autosomal recessive diseases: Xeroderma pigmentosum group F (XPF), Xeroderma pigmentosum type F/Cockayne syndrome (XPF/CS), Fanconi anemia, complementation group Q (FANCQ), and XFE Progeroid syndrome (XFEPS). In this paper, we present a case of a 53-year-old Caucasian female, with rare variants in the ERCC4 gene. When she was 42 years old, falls and loss of balance occurred. At the age of 48, occurred involuntary, uncoordinated movements of the upper limbs and head, tongue stereotypes (licking and extending movements), speech problems (dysarthria), memory deterioration, and hearing loss. From childhood, she has had hypersensitivity to UV radiation. The neurological examination revealed chorea syndrome, cerebellar ataxia, dysarthria, and bilateral hearing loss. She has numerous pigmented lesions on her skin. Brain MRI demonstrated massive cortico- subcortical atrophy. The neuropsychological examination revealed dysfunctions in the executive domain in terms of attention, working memory, organizing, and planning activities. The performed genetic diagnostics excluded spinocerebellar ataxia type 1, 2, 3, 6, 17, Huntington's disease, and FMR1 premutation . In the genetic analysis of Next Generation Sequencing (NGS), two variants: c.2395C> T and c.1349G> A in the ERCC4 gene were identified in a heterozygote configuration. So far, a few cases of ERCC4 gene variants, which are associated with nucleotide excision repair pathways, have been described in connection with symptoms of cerebellar ataxia. In patients with ERCC4 biallelic variants , the adult neurological phenotype can be sometimes the first symptoms and reason for access to genetic testing.The above case highlights the occurrence of rare genetic causes of progressive neurodegenerative diseases in adults, especially with the spectrum of autosomal recessive nucleotide excision repair pathway disorders (NERD).